Type 2 Diabetes Mellitus (T2DM) “Remission” in Non-bariatric Patients 65 Years and Older - Tangelloju, Srikanth; Little, Bert B.; Esterhay, Robert J.; Brock, Guy; LaJoie, A. Scott (Frontiers in Public Health, 2019)
Objective: To analyze the factors associated with type 2 diabetes mellitus (T2DM) “remission” in non bariatric Medicare patients 65 years and older Research Design and Methods: A retrospective cohort analysis of a Medicare Advantage health plan was conducted using administrative data. An individual was identified as T2DM if the individual had: ≥ 2 medical claims for T2DM coded 250.xx excluding type 1 diabetes; or ≥ 2 pharmacy claims related to T2DM; or ≥ 2 combined medical claims, pharmacy claims for T2DM in 12 months. A T2DM individual was in “remission” if they had no T2DM related claims for more than 12 months continuously. This is different from the standard American Diabetes Association definition of remission which includes HbA1c values and hence is represented in quotation (as “remission”). 10,059 T2DM individuals were evaluated over a period of 8 years from 2008 to 2015. Cox proportional hazards was used to identify significant variables associated with T2DM “remission.” Results: 4.97% of patients studied met the definition of T2DM “remission” in the study cohort. After adjusting for covariates this study found a number of variables associated with T2DM “remission” that were not previously reported: no statin use; low diabetes complications severity index score; no hypertension; no neuropathy; no retinopathy; race (non-white and non-African American); presence of other chronic ischemic heart disease (IHD) and females (p<0.05). Conclusion: T2DM “remission” in Medicare patients 65 years and older is observed in a community setting in a small proportion of non-bariatric patients.